APPLICATION OF INTERACTIVE FORMS OF STUDY IN THE PROCESS OF STUDYING THE DISCIPLINE "THERAPEUTIC DENTISTRY" UNDER THE CONDITIONS OF THE CREDIT-MODULE SYSTEM - Повшенюк, А.В.; Шінкарук-Диковицька, М.М.; Тепла, Т.О.; Касьяненко, Д.М.; Komnatskyi, B.Y. (World of Medicine and Biology, 2018)
At the practical classes with the fourth-year students of the dental faculty of the Vinnitsa National Pirogov Memorial Medical University used the method of debriefing with the elements of a business game in 82 Ukrainian-language students and the case-method in 85 students. The study of the discipline ended with the definition of current progress, carrying out the final module control and graded test. The result of the study showed that the obtained statistical data did not differ significantly (p> 0.05) and both methods of interactive learning showed very good results. However, the percentage of students who received "excellent" and "good" marks is almost 1.5 times higher in the group of students where training was conducted using the method of debriefing. Moreover, the level of demonstrated practical skills at the final module control of the students in this group was qualitatively different from the group where case method was applied. The use of interactive forms of student teaching provides the opportunity to improve mastering the actual material, improve the practical skills of the clinical application of theoretical knowledge and it facilitated the professionalization of students.